2021
DOI: 10.1177/1461444820953517
|View full text |Cite
|
Sign up to set email alerts
|

Storing and sharing: Everyday relationships with digital material

Abstract: Solid-state drives, Bluetooth capabilities, smartphones, “the cloud,” social media platforms, and other digital technologies have fundamentally altered how we share and store digital materials. This article sets an agenda for understanding how people manage the proliferation of digital material in their everyday lives through a close examination of the strategies and rituals different people around the world employ to organize, curate, or delete digital materials. Drawing upon findings from 11 articles, it con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…While psychology scholars couple different types of reading (sustained and reflective) with the temporal shifts afforded by different reading aims (long reading of fiction versus short reading for information), new media scholars, particularly those working in the critical literacy tradition, suggest that the depth and intensity of engagement with different types of texts is related to readers' subjectivities, which are created, sustained and propagated in different reading contexts. Horst et al (2021) suggest that readers' depth of engagement with a text relates to the different levels of digital labour invested in the text's production. Related to this argument, Theunissen and Favero (2021) describe how the ephemerality of digital texts is shaped by the friction in live-streamed texts, which are shown for a short time but then automatically archived and thus made durable .…”
Section: The Ephemerality Of Readingmentioning
confidence: 99%
“…While psychology scholars couple different types of reading (sustained and reflective) with the temporal shifts afforded by different reading aims (long reading of fiction versus short reading for information), new media scholars, particularly those working in the critical literacy tradition, suggest that the depth and intensity of engagement with different types of texts is related to readers' subjectivities, which are created, sustained and propagated in different reading contexts. Horst et al (2021) suggest that readers' depth of engagement with a text relates to the different levels of digital labour invested in the text's production. Related to this argument, Theunissen and Favero (2021) describe how the ephemerality of digital texts is shaped by the friction in live-streamed texts, which are shown for a short time but then automatically archived and thus made durable .…”
Section: The Ephemerality Of Readingmentioning
confidence: 99%
“…Digital sharing is complex as Horst et al (2021) detail. A particular aspect of our work in PNG centres on increasing use of social media as a way of communicating and sharing music, images, videos and information that has resulted in a demand for data.…”
Section: From Cassettes To Mp3 Filesmentioning
confidence: 99%
“…25 The EU Kids Online 2020 report indicated that across 19 European countries, less than 10% of children aged 12-16 had sent sexual messages or images over the previous year and there was variation across countries. 26 Some of the earliest work in this area presented a typology of sexting episodes which was derived from an analysis of over 550 cases obtained from a national survey of law enforcement agencies. 27 The cases all involved "images of minors created by minors" which met the criteria under US law for "child pornography".…”
Section: The Role Of Coercionmentioning
confidence: 99%